Synthesis, Characterization And Biological Significance Of Novel Schiff-Base 3d Metal Complexes (Journal of Pharmaceutical Negative Results, 2022)
The chemistry of metal complexes with tailor made Schiff base ligands and their applications, have aroused considerable interest mainly because of preparative accessibility and structural variability. Complexes of Co(II), Ni(II) and Cu(II) with the Schiff base ligands derived from 5-bromo-2-hydroxybenzeldehyde with 2-amino-4-chlorophenol (BHAP) and 2-aminothiazole (BHAT) have been synthesized and characterized by various physicochemical methods viz. micro-analytical data, UV-VIS, FT-IR, ESR Spectroscopy molar conductance and magnetic susceptibility measurements. All the complexes are colored and stable towards air and moisture. The Schiff base and metal complexes show a good activity against the bacteria; B. subtilis, E. coli and S. aureus and fungi A. niger, A. flavus and C. albicans. The antimicrobial results also indicate that the metal complexes are better antimicrobial agents as compared to the Schiff bases.